"Think About the Women!": The New Anti-Abortion Discourse in English Canada - Gordon, Kelly (Université d'Ottawa / University of Ottawa, 2011)
This thesis offers an overview of the new rhetorical strategies of persuasion being implemented by the contemporary English Canadian anti-abortion movement. This thesis analyzes the main arguments, philosophical principles, narratives and other important rhetorical strategies used by the contemporary anti-abortion movement in English-speaking Canada. It seeks, in other words, to explain how the anti-abortion movement talks to Canadians and how it attempts to persuade them of anti-abortion views.
Keywords: abortion; women's studies; discourse; anti-abortion movement